Experimental and Statistical Analysis of the Corrosion in Tendons in Contact With Water - Morales, Juan A.; Torres, Julio; Rebolledo, Nuria; Sánchez, Javier (Frontiers in Materials, 2019)
It is commonly mentioned that corrosion of steel in presstressed concrete can induce brittle failure. It is also understood that in order to estimate the presstressed structures service life is necessary to study the pitting factor that compares the maximum corrosion pit depth with the section loss by homogeneous corrosion. Results are presented on corrosion tests to measure the corrosion depth in tendons in contact with water. In present paper, a statistical analysis has been carried out in order to obtain the pitting factor for different cross sections submerged in water. The results indicate that the pitting factor value varies between 1.20 and 1.85 depending on the confidence interval considered, which can significantly reduce the service life of the presstressed tendons as long as the exposure conditions are those set out in this study.